Individual breastfeeding and weaning histories in a 19th century Spanish sample using stable isotope analysis of incremental dentine sections - Smith, Taylor (My University, 2018)
Through stable isotope analysis of human tooth dentine, this thesis investigates breastfeeding and weaning patterns in relation to rickets in a sample of sub-adults (n=12) interred in the nineteenth century sub-adult cemetery located at the Church of the Trinitarias in Madrid, Spain. The main objectives of this research are to create early life feeding histories for each individual using dentine serial sectioning techniques and apply these histories to investigate the relationship between breastfeeding, weaning, and vitamin D deficiency. The early life feeding histories allows for the determination of the onset and complete age of weaning at an individual level. These stable isotope data are then used to estimate general trends in breastfeeding and weaning practices in nineteenth century Spain. The results of this study indicate that the onset age of weaning for most of the individuals in this sample was between 10 and 14 months of age. The age at which breastmilk consumption stopped entirely was more difficult to estimate, however, in individuals that did show evidence of completed weaning, it was estimated to occur around the age of three. These ages are slightly higher than those discussed in historical sources for nineteenth century Spain. When these results are compared to contemporaneous, more industrialized, European countries the comparison shows that the initialization of weaning occurred slightly later and was a more gradual process in this Spanish sample. The results also demonstrate that there is no direct relationship between weaning patterns and the occurrence of skeletal vitamin D deficiency. It may be that the high prevalence of vitamin D deficiency is linked with the nuances of breastfeeding and other biocultural variables, such as a lack of sun exposure, an inadequate weaning diet, or childcare practices.
Keywords: Weaning; Breastfeeding; Paleopathology; Stable Isotopes